2012
DOI: 10.1136/archdischild-2011-301501
|View full text |Cite
|
Sign up to set email alerts
|

The impact of early identification of permanent childhood hearing impairment on speech and language outcomes

Abstract: It is well established that permanent childhood hearing impairment (PCHI) has a detrimental impact on speech and language development. The past two decades have seen the gradual introduction of universal newborn hearing screening (UNHS) programmes coupled with early intervention programmes. We review studies that have capitalised on the advent of newborn hearing screening to assess the impact of early identification of PCHI on language outcomes in deaf children. The research supports the conclusion that, in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 49 publications
3
80
1
6
Order By: Relevance
“…Despite the selective nature of this South Africa study sample (i.e. more privileged) critical periods for intervention, prior to 12 months of age, are not realized for children with profound hearing loss [26,31,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the selective nature of this South Africa study sample (i.e. more privileged) critical periods for intervention, prior to 12 months of age, are not realized for children with profound hearing loss [26,31,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…Hearing integrity in the first 3-4 years of life, the 'critical period' is essential for acquisition of speech and language. There is evidence that this is beneficial because early detection and management improve outcomes in terms of speech, language and education [3]. OME, associated with risk factors like recurrent URC, is considered the most common cause of silent hearing impairment among children.…”
Section: Introductionmentioning
confidence: 99%
“…The Wessex trial (Kennedy et al, 2006), showed that DHH children who had benefited from UNHS had significantly higher receptive language scores than comparable DHH children in the UK who had not been part of early trials. A recent review of the benefits of UNHS (Pimperton & Kennedy, 2012) reports consistent evidence from studies in Colorado and Australia showing that UNHS, and associated early diagnosis of hearing loss, does bring benefits for language development.…”
Section: Introductionmentioning
confidence: 99%